If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 66 = 4x + 32 Reorder the terms: 66 + 2x = 4x + 32 Reorder the terms: 66 + 2x = 32 + 4x Solving 66 + 2x = 32 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 66 + 2x + -4x = 32 + 4x + -4x Combine like terms: 2x + -4x = -2x 66 + -2x = 32 + 4x + -4x Combine like terms: 4x + -4x = 0 66 + -2x = 32 + 0 66 + -2x = 32 Add '-66' to each side of the equation. 66 + -66 + -2x = 32 + -66 Combine like terms: 66 + -66 = 0 0 + -2x = 32 + -66 -2x = 32 + -66 Combine like terms: 32 + -66 = -34 -2x = -34 Divide each side by '-2'. x = 17 Simplifying x = 17
| -6p-3(5-5p)=4(p-3)-43 | | =(x^2-12x+40)(x^2+6x+10) | | 3x^2+5x+6= | | 7x^2+30x-8=0 | | 8+5t=2t+14 | | 738-67x=6250 | | x/5-4=x/2+8 | | (-(1/2))^(-2) | | b+24=60 | | -9-5=5x+6-4x | | 18m^2-180mn+50N^2=0 | | x+.0507x=2300 | | 2z-1=180 | | x/24=-14+3 | | 3z=16-25 | | 16/38 | | B=ha | | (2x-3)(5x^2-6x+7)= | | 2v^2-v=6 | | C/g=Q+v/v | | -5(9x+9)= | | 8c+9c+2c-1= | | (3x^4)(2x^2)= | | 5/30t-24/30=6/30 | | 15a^2-6a^3= | | =4x^2-19x+12 | | Xsquared+7x-44=0 | | h=-8t^2+40t | | h=-8y^2+40t | | (y-1)(y+2)=(y-6)(y-4)+7 | | log[3](5x-7)=3 | | (3x-6)(2x-8)= |